Behavior of the Use of Mosquito Net as a Prevention of Malaria in Ondorea Village, Nanga Panda Sub-district - Paschalia, Yustina PM; Doondori, Anatolia K.; Irfan, Irfan; Kambuno, Norma Tiku (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: Malaria is an infectious disease that is still a world public health problem, especially in developing countries with tropical climates, including Indonesia. Ondorea Village in Nangapanda Subdistrict, Ende Regency, is one of the villages in East Nusa Tenggara, which is a province with APIs above the national average. Objective: To determine family behavior in using mosquito nets as an effort to prevent malaria in Ondorea Village, Nangapanda District. Method: This research is a survey research type with descriptive research design, the design used is"cross sectional".The population were all families residing in Ondorea Village, totaling 178 families, the sample in this study used a total sample. The variable in this study was a single variable, namely family behavior in the use of mosquito nets. The data used in this study are primary data collected by making home visits. Results: Public knowledge about the use of mosquito nets as an effort to prevent malaria in Ondorea Village, Nangapanda District was in the sufficient category, namely 85.39%, those with good knowledge of 6.34% and those with moderate knowledge of 7.87%. The public attitude about the use of mosquito nets is in the good category, namely 99.4%, which has a sufficient attitude of 0.56%. Conclusion: There is no relationship between the level of knowledge and the behavior of using mosquito nets, but it is found that there is a relationship between family attitudes and the behavior of using mosquito nets as an effort to prevent malaria